Volume 1: 22nd Biennial Conference on Mechanical Vibration and Noise, Parts a and B 2009
DOI: 10.1115/detc2009-87591
|View full text |Cite
|
Sign up to set email alerts
|

Switched Stiffness Vibration Controllers for Fluidic Flexible Matrix Composites

Abstract: This paper investigates semi-active vibration control using Fluidic Flexible Matrix Composites (F 2 MC) as variable stiffness components of exible structures. The stiffness of F 2 MC tubes can be dynamically switched from soft to stiff by opening and closing an on/off valve. Fiber reinforcement of the F 2 MC tube changes the internal volume when externally loaded. With an open valve, the uid in the tube is free to move in or out of the tube, so the stiffness is low. When the valve is closed, the high bulk modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, when the valve is closed, the F 2 MC tubes are very stiff since the high bulk modulus fluid resists the volume change due to the axial loading and the fiber orientation. In addition, it has been shown that active and semi-active valve control can be effective in modulus tuning [16] and vibration suppression [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, when the valve is closed, the F 2 MC tubes are very stiff since the high bulk modulus fluid resists the volume change due to the axial loading and the fiber orientation. In addition, it has been shown that active and semi-active valve control can be effective in modulus tuning [16] and vibration suppression [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the F 2 MC structures have been investigated for vibration and impedance control using simple on/off valve control. Lotfi-Gaskarimahalle and Rahn (2009) investigated the use of a zero vibration (ZV) state switch technique (open/closed-valve control) for the F 2 MC system and showed that an optimal ZV controller outperforms an optimal Skyhook controller for vibration control. While the current semi-active control method (on/off switching of valve) provides the adaptive structure with two modes of operation, i.e., soft or stiff, active control of a servovalve can significantly enhance the variability of the stiffness of the single and multicellular structures.…”
mentioning
confidence: 99%